Revisiting the “Keynes Plan” for an International Clearing Union in a Eurozone Perspective - Emmanouil-Kalos, Alkinoos (HAPSc Policy Briefs Series, 2020)
The last decade has been turbulent for the EMU, with many structural weaknesses becoming apparent. While in a state of emergency, the European Central Bank has had to “reinvent” itself in order to stabilize the Eurozone, while the vital importance of the imbalances between the member states has been recognized, as the establishment of the Macroeconomic Imbalances Procedure (MIP) indicates. Yet, it is widely acknowledged that the architecture of the Eurozone needs structural reforms. This policy brief aims to present the case for the adoption of the core ideas of the “Keynes Plan” for an International Clearing Union, which could function as an important first step towards fighting intra-eurozone imbalances, hence strengthening the EMU. Given the existence of the European Central Bank and the common currency, a moderate version of such a plan could be implemented even without the need for any changes in the EU treaties, and could be the stepping stone for further economic integration.